PENEGAKAN HUKUM LINGKUNGAN TERHADAP PENEGAKAN EKOSISTEM KAWASAN HUTAN LINDUNG - Harris, Algazali; Maskun, Maskun; Aspan, Zulkifli (UNES Law Review, 2023)
Deforestation causes the availability of forest land for ecosystem and environmental, Forest management activities in Indonesia have been regulated in Law Number 41 of 1999 concerning. The Forestry Law states that all forests within the territory of the Republic of Indonesia, including the natural wealth in them, are controlled by the state for the greatest prosperity of the people. there is an environmental law enforcement agency appointed to supervise or take action against illegal loggers as well as a forest use licensing mechanism, however, the facts on the ground show that there are still many forestry activities that damage forest ecosystems and are even increasing. This research was conducted at the Kalaena Forest Management Unit (KPH) which carried out supervision in the Protected Forest Area area, This research is Empirical Research. The data used are primary, secondary and tertiary data. All data and materials obtained from the results of the research were compiled and analyzed qualitatively and presented descriptively.